Vitamin D Receptor-Dependent Protective Effect of Moderate Hypoxia in a Mouse Colitis Model - Wang, Zheng; Yang, Hong; Lv, Hong; Huang, Changzhi; Qian, Jiaming (Frontiers in Physiology, 2022)
Although hypoxia is important for maintaining the intestinal barrier, its effect on the barrier during acute colitis and the underlying mechanisms are not fully understood. To explore the influence of hypoxia in dextran sulfate sodium (DSS)-induced colitis mice and the role of hypoxia-inducible factor (HIF) and vitamin D receptor (VDR) in the process. Colitis mice were subjected to hypoxia to detect intestinal barrier function changes. And the mechanisms were explored in vitro. First, compared with colitis mice without hypoxia stimulation, those with hypoxia stimulation showed significantly decreased pathological damage and improved permeability of the intestinal barrier. The expression of tight junction proteins (occludin, ZO-1), HIF-1α and VDR were up-regulated in colitis mice with hypoxia stimulation. However, in VDR gene knockout (KO) colitis mice, hypoxia treatment showed no protective effect, suggesting the VDR dependency of this effect. Similarly although hypoxia stimulation could enhance the single-layer epithelial transmembrane electrical resistance in DLD-1 cells, these effects disappeared in VDR-knockdown cells. Furthermore, over-expression of HIF-1α in DLD-1 increased the expression of VDR, while HIF-1α-knockdown reduced the VDR expression directly. Chromatin immunoprecipitation and luciferase assays confirmed that HIF-1α can bind to the promoter region of the VDR gene under hypoxia. Finally, compared with their wild-type siblings, VDR-KO mice showed reduced abundance of anaerobic bacteria and SCFA-producing bacteria. Hypoxia was protective against DSS-induced colitis, and VDR is instrumental in it. Furthermore, HIF-1α-VDR mediates the effect of hypoxia on the barrier function. Moreover, intestinal flora may be an important link between hypoxia and VDR.